Strega Nona meets her match - DePaola, Tomie, 1934- (New York : Putnam & Grosset Group, 1996)
A rival puts Strega Nona out of the healing business until Big Anthony's assistance inadvertently sabotages the newcomer in his usual well-meaning way.
"PaperStar.".
Elem. School Library Collection.
Publisher's Weekly.
School Library Journal.
3.9.
3.9
Keywords: Witches -- Fiction; Witches -- Fiction